Acoustic Method of On-Site Examination of Ceramic Long-Rod Insulators - Ranachowski, P.; Rejmund, F.; Fleszyński, J. (Engineering Transactions, 2004)
This paper presents the new non-destructive ultrasonic method for investigation of long-rod insulators working as the element of station isolating switches. The 110/6 kV stations belonged to domestic industrial power engineering. The main aim of the research was to establish a close correlation between the degree of defectiveness of electrotechnical porcelain and parameters of ultrasonic wave propagation and attenuation. In addition, the causes of breakage of insulator SWZPAK-110 from the year 1975 were ascertained. This ceramic element underwent detailed structural and comparative acoustic measurements. The experimental investigations were per-formed using a specially designed and constructed measuring equipment. Besides founding the original technological and also direct causes of breakage of the insulator mentioned above, the most significant achievement of the work was elaboration of the methodology of ultrasonic measurements applied directly to objects in exploitation. The presented method was used for the analysis of quality of the group of 43 insulators after long-term exploitation on isolating switches.